PENGARUH AIRLINE IMAGE DAN WORD OF MOUTH TERHADAP PURCHASE INTENTION PADA PENGGUNA MASKAPAI PENERBANGAN LION AIR KOTA BANDA ACEH - Farah Mutia Sari; Syarifah Evi Zuhra (Departemen Manajemen, 2019)
This study aims to measure the influence of Airline Image and Word of Mouth on Purchase Intention on Lion Air users in Banda Aceh City. The sample used in this study amounted to 129 respondents. The equipment in collecting data in this study used questionnaires that were distributed manually and Google Form. The technique used in sampling was purposive sampling. In this study. Multiple Linear Regression method were used as an analytical method to see the influence of all the variables involved. Based on the regression results, it indicates that Airline Image has a positive effect on Purchase Intention, Word of Mouth has a positive effect on Purchase Intention, and Airline Image and Word of Mouth have a simultaneous effect on Purchase Intention.